2015
DOI: 10.1002/jcb.25271
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Effects of AMPK on Insulin Gene Expression and Glucose‐Induced Insulin Secretion

Abstract: The activation of AMP-activated protein kinase (AMPK) is known to repress the expression of the insulin gene and glucose-stimulated insulin secretion (GSIS). However, the mechanisms by which this occurs, as well as the effects of AMPK activation on glucolipotoxicity-induced β-cell dysfunction, have not been elucidated. To investigate the effects of 5-amino-4-imidazolecarboxamide ribonucleotide (AICAR) and peroxisome proliferator-activated receptorγ-coactivator-1α (PGC-1α) on β-cell-specific genes under glucoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…A recent study suggested that Sirt1 deacetylates PPARγ during energy deprivation and deacetylated PPARγ then interacts with Prdm16 to alter the balance from energy storage to energy expenditure (Qiang et al, 2012). Moreover, overexpression of PGC1α suppresses NeuroD1 mRNA expression in isolated rat and human islets (Kim et al, 2016). Similarly, we found that deletion of IRE abolished the regulation of PGC1α by Prdm16, suggesting that Prdm16 directly binds the PGC1α promoter region.…”
Section: Discussionsupporting
confidence: 63%
“…A recent study suggested that Sirt1 deacetylates PPARγ during energy deprivation and deacetylated PPARγ then interacts with Prdm16 to alter the balance from energy storage to energy expenditure (Qiang et al, 2012). Moreover, overexpression of PGC1α suppresses NeuroD1 mRNA expression in isolated rat and human islets (Kim et al, 2016). Similarly, we found that deletion of IRE abolished the regulation of PGC1α by Prdm16, suggesting that Prdm16 directly binds the PGC1α promoter region.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, previous exercise training was already showed to prevent the renal and cardiac damage in a model of DM [Silva et al, ]. Our exercise protocol increased the O 2 consumption induced by succinate and ADP by the skeletal muscle of Ex STZ relative to Sed STZ mice probably associated with increase on mitochondrial biogenesis as showed by increased on PGC‐1 α levels [Kim et al, ]. Moreover, the H 2 O 2 production induced by succinate was higher in Ex STZ mice.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, the activation of AMPK in adipocytes has been shown to suppress lipogenesis while promoting energy dissipation suggesting potential antiobesity effect [ 118 ]. Even though some studies still show the paradoxical nature of the AMPK activation in glucose and lipid metabolism, mostly related to the level of stimulation (chronic verses acute) (e.g., [ 119 , 120 ]), the role of AMPK activators in various disease condition have been well documented [ 121 ]. In a recent review [ 122 ], the antidiabetic potential of natural products such as anthocyanins through effect on the AMPK and insulin-signaling pathways have been highlighted.…”
Section: General Summary and Discussionmentioning
confidence: 99%